Konsep Islam Dan Iman Muhammad Syahrur (Studi Kritis) - Faiz Ramdani Sholahuddin (Tasfiyah: Jurnal Pemikiran Islam, 2018)
This paper tries to discuss a matter of aqeedah including Iman (Islamic Belief) and Islam which was concepted by Muhammad Syahrur. This matter is important due conclusions regarding consequences it has, especially in building aqeedah, akhlaq (Islamic morality), and sharia of a Muslim. This study is focused on discussing the concept of Islam and Iman created by Muhammad Syahrur including terms, concepts, his basis of argumentation, and his way how Syahrur came to a conclusion. On the other hand, in addition to its descriptive style, this paper also tries to present criticism, as a counterweight effort—or perhaps as an alternative to what Syahrur offers.